Narrative form of European art cinema : the case of The Double Life of Veronique (1991) and Antonia's Line (1995) / Norlela Ismail - Ismail, Norlela (UPENA, 2007)
If a comparison is to be made between the anti-classical and the classical narrative, which one is the fairest' of all? Each form has its own distinct features and their sheer existence is due to the upheaval point of views about film as cultural identity among film scholars in the early twentieth century. Most European films are believed to have employed the anti-classical narrative whilst mainstream films or referred to as Hollywood films favour the classical narrative. The purpose of this article is to identify the types of film narrative form of European art films. Two films are used as case studies: The Double Life of Veronique (1991) and antonia's Line (1995). The key concepts examined are story/plot and character's motivations. Film style is briefly discussed to reinforce further understanding of the key concepts. This study shows that The Double life of Veronique (TDLOV) offers a unique narrative form that differs from that of Antonia's Line in terms of plot construction and character's motivations. There are more narrative gaps found in TDLOV as compared to Antonia's Line. TDLOV has demonstrated a loose chain of events, while characters are not motivated, not to mention its ambiguous ending. On the other hand, Antonia's Line shows that the main character has a goal to achieve with events found to have linked to one another, while its denouement is clear.